SERRA DA CAPIVARA/PI NATIONAL PARK AND THE PRACTICE OF ECOTOURIST ACTIVITY - Barros, Juliana Ramalho; Aguiar Junior, Paulo Roberto Ferreira de; Santos, Mayra Nayara Nair dos; Santos, Nicali Bleyer Ferreira dos (Mercator, 2023)
Ecotourism faces the challenge of balancing environmental and cultural preservation with sustainable development and local income generation. Since the Stockholm Conference in 1972, environmental conservation has gained relevance on government schedule. The establishment of Conservation Units (CUs) has led to the implementation of administrative and political mechanisms to safeguard specific ecosystems. These spaces not only protect the environment but also enable indirect use through tourism, with an emphasis on ecotourism. This study aims to evaluate whether the ecotourism practices adopted in the Serra da Capivara National Park (PNSC), located in Piauí, align with the theoretical framework that underpins this tourism segment. Using a Case Study methodology, which includes visits to PNSC, literature review, and photographic documentation, it was found that this Integral Conservation Unit is in line with the guidelines advocated by ecotourism. Keywords : Conservation Unit; Serra da Capivara National Park; Ecotourism.